The Immune Interface of Age: Neonatal and Adult Host Responses to Monkeypox Virus Infection - Sharma, Priya; Chauhan, Aakhya; Das, Ishika; Chattaraj, Amartya; Yadav, Pardeep (Journal of Neonatal Surgery, 2025)
The emerging zoonotic pathogen Monkeypox virus (MPXV) produces separate clinical outcomes between age groups because young and older individuals possess varying levels of immune system development. The review examines the host-specific events that occur in both adult and newborn immune systems when exposed to Monkeypox virus. Neonates experience suspicion to systemic spread, limited interferon responses and subpar viral clearance because they have underdeveloped immune systems. The immune system of adult hosts generates strong Th1-dominated defense mechanisms which result in better viral control. High-grade immune reactions in adults may create tissue damage in major infection manifestations. The evaluation investigates how aging affects skin protection mechanisms and the way cytokines work and antigen-presenting cells perform their responsibilities. Medical treatments with appropriate age considerations and vaccination administration strategies and public health policies need accurate understanding of age-specific immune properties. The understanding of immunological age interactions enables researchers to develop individualized interventions which will enhance outcomes for various patient groups throughout MPXV outbreaks.